Haiyfa Lekor Enterprise / Yusri Azizan ... [et al.] - Azizan, Yusri; Mohd, Fazly Amri; Wan Hussin, Wan Mohammad Hamdan; Saarin, Sharzelina; Birkamsin, Nor Aisyah (Faculty of Architecture, Planning, 2006)
Firstly, our Company name is HAIYFA LEKOR ENTERPRISE. Our Company get the name "HAIYFA" from combination of the first letter of the business partner name (HA-Hamdan, I-Ina, Y-Yusri, F-Fazly and A-Aisyah) and LEKOR ENTERPRISE is our Company nature of business. That means, our nature of business is producing and supplying keropok lekor to the all districts in Terengganu. Our Company is based on Partnership Company.